2017
DOI: 10.1002/pd.5018
|View full text |Cite
|
Sign up to set email alerts
|

Smith–Lemli–Opitz syndrome carrier frequency and estimates of in utero mortality rates

Abstract: ObjectiveTo tabulate individual allele frequencies and total carrier frequency for Smith–Lemli–Opitz syndrome (SLOS) and compare expected versus observed birth incidences.MethodsA total of 262 399 individuals with no known indication or increased probability of SLOS carrier status, primarily US based, were screened for SLOS mutations as part of an expanded carrier screening panel. Results were retrospectively analyzed to estimate carrier frequencies in multiple ethnic groups. SLOS birth incidences obtained fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…Based on disease classification databases, HGMD and ClinVar, carrier frequencies were 0.2–0.3% in East Asians and 0.6% in Koreans. Compared with previous studies on East Asians, carrier frequency in gnomAD is located between the previous reports (0.1 to 1.6%) [ 9 , 10 ].…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Based on disease classification databases, HGMD and ClinVar, carrier frequencies were 0.2–0.3% in East Asians and 0.6% in Koreans. Compared with previous studies on East Asians, carrier frequency in gnomAD is located between the previous reports (0.1 to 1.6%) [ 9 , 10 ].…”
Section: Discussioncontrasting
confidence: 73%
“…As the 2015 ACMG-AMP guideline is more stringent in variant classification, a previous study has shown a relatively higher carrier frequency than this. In another study, 13,546 East Asians were analyzed, of which 3102 East Asians were analyzed using next-generation sequencing (NGS), and another 10,444 were analyzed using targeted genotyping that could only identify 13 major DHCR7 variants [ 10 ]. The carrier detection rate according to the method difference was different for each ethnic group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical specificity is expected to be high, 28 and even if clinical sensitivity were <100%, the results of our cost-effectiveness analysis would not be impacted because the clinical benefit measurements (i.e., the denominator in the cost-effectiveness equation) rely only on variants known to be pathogenic and are not affected by the undetected or incorrectly classified pathogenic variants that decrease clinical sensitivity. Third, though miscarriage can be common for certain diseases (e.g., Smith–Lemli–Opitz syndrome 40 ) and may impact cost estimates, we expect this impact to be minor because few diseases and variants yield higher miscarriage rates.…”
Section: Discussionmentioning
confidence: 99%